How do households respond to expected inflation? An investigation of transmission mechanisms - Janet Hua Jiang; Rupal Kamdar; Kelin Lu; Daniela Puzzello (Bank of Canada, 2024)
We disentangle the channels through which inflation expectations affect household spending. We conduct a survey featuring hypothetical scenarios that generate a controlled increase in inflation expectations. For 74% of households, current spending is unresponsive, typically due to fixed budget plans or irrelevance of inflation expectations. About 20% of households reduce spending, often citing wealth effects, nominal income rigidity, and inflation hedging. Only 6% increase spending, mostly due to intertemporal substitution or stockpiling. Respondents who expect other economic variables to deteriorate are more likely to reduce spending. Our findings suggest manipulating inflation expectations to boost consumer spending may not be an effective policy tool.
Keywords: D15; D84; E2; E52; E7; 330; Central bank research; Inflation and prices; Inflation targets; Monetary policy; Monetary policy transmission